Zwitterionic dual-network strategy for highly stretchable and transparent ionic conductor. (28th September 2021) - Lan, Ji; Zhou, Bo; Yin, Chenxiao; Weng, Lin; Ni, Wei; Shi, Ling-Ying
Abstract: The development of flexible electronic devices depends on the research of stretchable conductive materials. In this work, we report a green and transparent ionic conductor with high stretchability based on green deep eutectic solvents (DESs) and biocompatible zwitterionic polymer. The dual-network (DN) strategy was achieved by two-step UV-initiated polymerization, and the DN ion gels consisting of the physically cross-linked zwitterionic poly(3-dimethyl(methacryloyloxyethyl) ammonium propane sulfonate) (PDMAPS) and chemically cross-linked poly(2-hydroxyethyl methacrylate) (PHEMA) were prepared, using choline chloride/ethylene glycol (ChCl/EG) DESs as solvents. The prepared DN ion gels present outstanding tensile properties (breaking strain over 1000%), high transparency (>90%), good room temperature ionic conductivity (0.315 S m −1 ), and good fatigue resistance. In addition, due to the ultra-low volatility and low freezing point of the ChCl/EG DESs, the DN ion gel shows high stability and frost resistance (−60 °C). Finally, the performance of the DN ionic gel-based flexible strain sensor is investigated to evaluate its application potential in wearable flexible electronic devices. The DN ion gel strain sensor can sensitively and stably monitor human motions. The outstanding characteristics such as non-toxicity and biocompatibility of both the conductive filler and polymer matrix for preparing the DN ion gels in this work provide a new view for the development of green flexible conductive devices with high performance and multiple functions. Graphical abstract: By a two-step UV-initiated polymerization method from the biocompatible monomers in green deep eutectic solvents, a series of transparent DN ion gel conductors with high stretchability (>1000%), good ionic conductivity (0.315 S m −1 at room temperature), high stability and excellent frost resistance (−60 °C) were prepared, which show great application potentials in wearable flexible electronic devices to sensitively and stably monitor human motions. Image 1 Highlights: Photoinitiated polymerization from biocompatible monomers using DESs solvents produces green stretchable ionic conductors. Significant improvements in strength and stretchability of the ion gels were achieved by the dual-network strategy. Zwitterionic network in the DN gel improves the conductivity and elasticity. The ultra-low volatility and low freezing point of the DESs ensure the good stability and frost resistance of DN ion gels. The prepared DN ion gel strain sensors present high sensitivity, accuracy and stability in monitoring human motion.